ESP IN PRACTICE SPEAKING: COMBINING TIME TOKEN TECHNIQUE WITH YOUTUBE VIDEO - Kurnia, Kurnia; Hafid, Haeruddin (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Teaching speaking in english for specific purpose, sometimes students are having difficult to engage with the activity, as they face problems like vocalized pause, lost idea, and having low confidence to speak as well as monotous activity that still dominate the teaching and learning process. In serious condition, Imitation and repetition technique used by the lecturer all the time. To overcome the problem, this research offered solution by combining time token technique with youtube video to increase students achievement in speaking. The population of the research were the second semester students of Management in STIE Muhammadiyah Mamuju academic year 2018/2019. The instrument used in the research was pre test and post test to measure students achievement after giving treatment using time token technique with youtube video. The result of the research showed that this technique can affect students’ speaking achievement significantly as shown in test result. It is proved by the difference between pretest and post-test result of the three components of speaking ability and final score of the students speaking ability. This technique can be a good alternative way to varying teaching of speaking.